2018
DOI: 10.1007/s00401-018-1859-2
|View full text |Cite
|
Sign up to set email alerts
|

Aging alters the immunological response to ischemic stroke

Abstract: The peripheral immune system plays a critical role in aging and in the response to brain injury. Emerging data suggest inflammatory responses are exacerbated in older animals following ischemic stroke; however, our understanding of these age-related changes is poor. In this work, we demonstrate marked differences in the composition of circulating and infiltrating leukocytes recruited to the ischemic brain of old male mice after stroke compared to young male mice. Blood neutrophilia and neutrophil invasion into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
178
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(192 citation statements)
references
References 104 publications
13
178
0
1
Order By: Relevance
“…This was accompanied by a greater influx of peripheral leukocytes, particularly neutrophils ( Figure 4D), which are the strongest producers of reactive oxygen species (ROS) and matrix metallopeptidases (MMPs) and promote neuronal injury and BBB disruption [124][125][126] . In agreement, an increased number of neutrophils with altered phenotypic responses was previously seen in aged male mice and human stroke patients compared to their younger counterparts 127 and an increased neutrophil to lymphocyte ratio has been associated with stroke severity and outcome 128 . Although the absence of neuroprotective signal in bulk tissue does not rule out the possibility of its presence in individual cell types, these results suggest that an increased neuroinflammation and infiltration of circulating immune cells are one of the primary drivers for the exacerbated pathology in aged mice.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This was accompanied by a greater influx of peripheral leukocytes, particularly neutrophils ( Figure 4D), which are the strongest producers of reactive oxygen species (ROS) and matrix metallopeptidases (MMPs) and promote neuronal injury and BBB disruption [124][125][126] . In agreement, an increased number of neutrophils with altered phenotypic responses was previously seen in aged male mice and human stroke patients compared to their younger counterparts 127 and an increased neutrophil to lymphocyte ratio has been associated with stroke severity and outcome 128 . Although the absence of neuroprotective signal in bulk tissue does not rule out the possibility of its presence in individual cell types, these results suggest that an increased neuroinflammation and infiltration of circulating immune cells are one of the primary drivers for the exacerbated pathology in aged mice.…”
Section: Discussionsupporting
confidence: 81%
“…These results indicate the involvement of other contributors, such as the early-infiltrating peripheral leukocytes. Previously, the hematopoietic component has been identified as a major source of IFN-I signaling following traumatic brain injury 136 and aged mice with bonemarrow transplants from young mice have improved stroke outcome 127 . In concordance, we detected greater upregulation of granulocyte signature genes in aged animals ( Figure 4D).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that phagocytic capacity is downregulated in senile microglia/macrophage. When hemorrhagic stroke occurs, the inflammatory milieu further limits phagocytic activities of microglia/macrophage, exacerbating disease severity of hemorrhagic stroke . Therefore, aging is an independent risk factor of both ischemic and hemorrhagic stroke and indicates detrimental disease outcomes .…”
Section: Inflammasome Activation Intensifies Neural Inflammation Aftementioning
confidence: 99%
“…When hemorrhagic stroke occurs, the inflammatory milieu further limits phagocytic activities of microglia/ macrophage, exacerbating disease severity of hemorrhagic stroke. 56 Therefore, aging is an independent risk factor of both ischemic and hemorrhagic stroke and indicates detrimental disease outcomes. 57 On the other hand, prognosis of stroke is largely dependent on the intensity of post-stroke neural inflammation.…”
Section: Infl Amma Some Ac Tivati On Intens Ifie S Neur Al Infl Ammmentioning
confidence: 99%
“…Although the function of BM-derived Iba1 + cells remains unclear, these cells have recently been attributed towards tissue repair and restoration of function following injury [23,24]. Interestingly, these beneficial effects are only observed when animals are recipients of young BM, but not old, presumably because old BM cells acquire a senescent-like phenotype upon migration to the injured brain [25]. Here, we hypothesize that the introduction of young microglia into the aged and irradiated brain may be beneficial for attenuating cognitive decline following radiotherapy.…”
Section: Introductionmentioning
confidence: 99%